A review of trends in scientific coverage of water governance in South Africa and what this means for agenda-setting of public investment in water governance R&D - Jacobs-Mata, Inga; Mukuyu, Patience; Dini, J. (Academy of Science of South Africa, 2021)
A review of global trends in water governance reveals a paradigm dominated by political and institutional change which becomes increasingly aligned with global shifts towards sustainability and also a rapid decline in the hydraulic mission. Closely aligned to these trends, but distinct in its own trajectory, South Africa’s water governance dynamics have evolved through a period of considerable socio-political change marked by inequitable resource allocation and water scarcity. This paper presents the results of a review of water governance research and development (R&D) trends in South Africa, aimed at informing the national funding agency – the Water Research Commission (WRC) – in its agenda-setting process for future water governance research. Through a bibliometric analysis, a data-mining exercise, and stakeholder consultations, this paper distils four key areas of focus for the future of water governance research in South Africa: (i) that future water governance research needs to be more needs-based, solution-oriented and embedded within real-life contexts; (ii) the need for a paradigm shift in water governance research to a constructive, adaptive and rapid response research agenda in an environment of increasing change and uncertainty; (iii) the need for the enabling environment to be strengthened, including acknowledgement of the role of individuals as agents of change, and the role of WRC in establishing a community of practice for water governance experts that can respond to issues with agility; and (iv) a consolidation of fragmented project-based knowledge to a programmatic approach that builds the pipeline of expertise in the water governance R&D domain.